1998
DOI: 10.1183/09031936.98.12061327
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of anti-inflammatory corticosteroids in human bone-derived osteoblast-like cells

Abstract: While effects of inhaled corticosteroids on serum markers of bone metabolism in normal and asthmatic subjects have been reported, there are little data on the direct effects of these corticosteroids on end-organs such as bone. The results presented here compare the effects of budesonide and its epimers (22S- and 22R-budesonide), fluticasone and dexamethasone on growth and differentiation of cultured human bone cells. Osteoblast-like cells were cultured from human foetal bone chips grown to confluence and used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Fluticasone is a more potent corticosteroid in inhibiting inflammation [22], and our data reflect this fact. It is also interesting to note that, although IL-8 is released more abundantly than IL-6 [23], this selective inhibition suggests that IL-8 may at least in part be steroid insensitive, and other studies have also demonstrated that certain cytokines are steroid insensitive [24, 25].…”
Section: Discussionsupporting
confidence: 81%
“…Fluticasone is a more potent corticosteroid in inhibiting inflammation [22], and our data reflect this fact. It is also interesting to note that, although IL-8 is released more abundantly than IL-6 [23], this selective inhibition suggests that IL-8 may at least in part be steroid insensitive, and other studies have also demonstrated that certain cytokines are steroid insensitive [24, 25].…”
Section: Discussionsupporting
confidence: 81%
“…Similar to the effects seen with BzATP, the patient’s cells responded in a paradoxical manner when treated with 1,25-dihydroxyvitamin D. Usually with increasing concentrations of 1,25-dihydroxyvitamin D, osteoblast cell proliferation decreases 6,10 and this was seen in the control biopsy cells. The patient cells, however, significantly increased proliferation in culture with a concentration of 10 −9  mol·L −1 1,25-dihydroxyvitamin D concentration( P <0.001; Figure 3c).…”
Section: Resultsmentioning
confidence: 51%
“…Cells were plated into 96-well plates at 1×10 5 cells per well and incubated at 37 °C for 24 h. The medium was then replaced with serum-reduced OptiMEM media and further incubated for 24 h, before the addition of treatments (benzoylbenzoyl-ATP (BzATP) or 1,25-dihydroxyvitamin D in vehicle) for another 24 h. Tritiated thymidine (final concentration 20 nCi·μL −1 ) was added to each well and incubated for 4 h. Cell proliferation was indirectly determined by the incorporation of tritiated (methyl,1′2- 3 H) thymidine, as previously described. 6 Scintillation vials were read for 5 min in a liquid beta-scintillation counter (Packard Tri-Carb 1990CA, Packard Instrument Company, Downers Grove, IL, USA). A bicinchoninic acid (BCA) assay was also carried out for cell proliferation measuring the amount of protein per well, in accordance with the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If there is systemic absorption of inhaled corticosteroids, it is possible that there are unwanted effects on bone, because osteoporosis is a major long‐term side‐effect with oral corticosteroids. We investigated the effects of fluticasone and budesonide on human osteoblast‐like cells in vitro 16 and found that the rank order of potency was fluticasone > budesonide, reflecting the same order as for suppression of the hypothalamic–pituitary–adrenal axis 14 and for clinical efficacy 17 . These findings suggested that the more potent inhaled corticosteroids, such as fluticasone, are likely to be more potent in terms of unwanted effects if there is systemic absorption.…”
Section: Inhaled Corticosteroidsmentioning
confidence: 99%